209 - The Impact of Function Focused Care in Assisted Living Communities in the United States during the COVID-19 Pandemic. (October 2021) - Galik, Elizabeth; Resnick, Barbara; McPherson, Rachel; Vigne, Erin
Abstract : The purpose of this study was to test the preliminary effectiveness and feasibility of implementation of a function focused care intervention, referred to as Function Focused Care for Assisted Living Using the Evidence Integration Triangle in Assisted Living Communities with Residents with Dementia, and consider the impact of COVID-19 restrictions on incidences of COVID-19 and worsening of behavioral symptoms. The intervention was designed to facilitate a philosophy of care in which staff are educated and helped to actively engage residents in functional and physical activity during all care interactions. This was a single group pre-post intervention study including 51 assisted living communities in a single state in the United States. The communities ranged in size from 8 to 50 beds with the mean number of beds being 13.25 (SD=7.69). The majority (99%) were for profit. There was significant improvement in the support of the environments (p=.01) and policies (p=.04) for physical activity. There was no significant change in falls, emergency room transfers, hospitalizations or nursing community transfers over time. Overall there were only 7 (18%) communities that had COVID-19 positive patients with the numbers ranging from 1-16 residents and percentage ranging from 0-31% and a mean percentage of 17%. The majority did not require that the residents quarantine in their rooms (87%) although they did restrict visitation with the exception of 3 (8%) communities that let families visit after training and with exposure and symptom risk assessments completed at each visit. Communities in which residents were quarantined in their rooms had a 40% greater likelihood of having COVID-19 positive residents than communities that did not quarantine residents. None of the restrictions imposed were associated with worsening of behavioral symptoms. The findings are descriptive and pilot in nature but can be used to guide future research around prevention and management of infections in assisted living.